Bioeconomic and greenhouse gas emissions modelling of the factors influencing technical efficiency of temperate grassland-based suckler calf-to-beef production systems. (August 2020) - Taylor, R.F.; McGee, M.; Kelly, A.K.; Crosson, P.
Abstract: The objective of this study was to investigate the relative importance of key performance metrics for temperate grassland-based suckler calf-to-beef production systems on farm economics and greenhouse gas (GHG) emissions. The approach was to use data obtained from commercial farms participating in a farm improvement programme to parameterise a whole farm systems bioeconomic model. This model was then used to evaluate the biotechnical, financial and GHG emissions effects of variation in key performance metrics including calving rate, calving date, cow replacement rate, progeny live weight gain and age at slaughter. Age at slaughter and calving rate had the greatest effect on costs of production per kilogram of carcass weight. Calving rate was also the most influential parameter affecting net margin (NM) with a change of 10 percentage units (from 0.75 to 0.85 calves per cow per year) resulting in NM increasing by +€84 per hectare (ha). Age at slaughter had the greatest effect on GHG emissions; increasing slaughter age by eight months, resulted in GHG per farm increasing from 23.5 to 31.6 carbon dioxide equivalents (CO2 e)/kg carcass. Although, combining high performance levels among all key performance metrics led to the greatest profitability and lowest emissions per kg carcass, the relative effects of individual parameters are not additive. This highlights interdependencies between production parameters for suckler calf-to-beef production systems. Graphical Abstract: Analysis of pastoral suckler beef cow production systems as modelled using the Grange Beef Systems Model. This graph shows net margin per hectare (dark bars) and total greenhouse gas emissions per kg carcass weight produced (dashed triangle) for a baseline system (BASE) and systems representing high calving rate (HCR), low calving rate (LCR), early calving date (ECD), late calving date (LCD), high replacement rate (HRR), low replacement rate (LRR), early finishing (EF), late finishing (LF), high average daily gain (HADG), low average daily gain (LADG), high production efficiency (HIGH) and low production efficiency (LOW). Unlabelled Image Highlights: We modelled the bioeconomic and GHG emissions effects of performance variation for suckler beef cow farms. Age at slaughter and calving rate had the greatest effect on costs of production. Calving rate was also the most influential parameter affecting profitability. Age at slaughter had the greatest effect on GHG emissions. The relative effects of individual parameters were not additive in respect of profitability and GHG emissions.